Prevalence of Depression Among Elderly Population in India - A Systematic Review & Meta-Analysis - Bincy K; Pradeep MVM; Padmavathy L; Ezhilmuthalvan A; Prashanth S; Logaraj M; Nalini V; Mahesh Kumar (Medsci Publications, 2024)
Background: Depression among the elderly is a global public health concern, impacting quality of life and overall well-being. However, there is a lack of recent systematic reviews or meta-analyses on its prevalence in India. This study aims to update this information through a systematic review and meta-analysis. Methods: The study utilized the Geriatric Depression Scale (GDS) as a screening tool for depression among individuals aged 60 and older in India, utilizing electronic databases for community-based cross-sectional studies from inception to date. Pooled prevalence with 95% CI was performed using R statistical software. Results: 23 community-based cross-sectional studies were included representing 13 Indian states, meeting the inclusion criteria. The combined prevalence of depression among the elderly was estimated to be 47% (95% CI: 0.39; 0.55), with significant heterogeneity observed among studies (I²=98%, p<0.01). The study underscores the considerable depression issue among India's elderly population, emphasizing the urgent need for tailored mental health interventions. Conclusion: The meta-analysis reveals a high prevalence of depression among India's senior population, highlighting the need for targeted public health initiatives to address this growing crisis and support the mental health needs of the elderly.